English Students’ Difficulties in Understanding Listening Section of the TOEFL Test - Dandika Aprino; Elfrida Elfrida; Azhar Aziz Lubis (Journal of English Education and Teaching, 2022)
The objective of this reseach is to find out the difficulties and the dominant factor that faced by the English students in understanding the listening section of the toefl test. This research used descriptive quantitative method. 18 students as the total population and 18 students become a sample of this research. The instrument of the reasearch was questionnaire adopted from Hamouda in Raini (2019). The questionnaire consist of 27 statements and devided into 7 tables. The result of this research shown that the highest percentage by using mean is in physical setting (50%) and the dominant factor is in physical setting (50%) where the problem that were the difficulty to concentrate with noises around and unclear sounds from poor quality-CD player are the biggest difficulties to the English students UNIB. It could be concluded that the content of listening test and physical setting become the highest difficulties and the dominant factor that faced by English Students UNIB. It was recommended for the  English lecturer should pay more intention towards to listening material and find more suitable method or technique in teaching listening course and students should find another option to cover the listening skill.